2021
DOI: 10.1016/j.jcjd.2020.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Being Physically Active: A Qualitative Study of Young People With Type 1 Diabetes and Their Parents

Abstract: Background: Benefits of physical activity are well recognized for youth with type 1 diabetes (T1DM), however being active is challenging. This study aimed to investigate the challenges experienced by adolescents, their parents and young adults with T1DM when they are physically active.Methods: Six focus groups involving adolescents (13-18 years; n = 14) and young adults (19-25 years; n= 7) and four focus groups with parents (n = 14) of the adolescents (13-18 years) were conducted. Data were analysed using cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…It has also been noted that children with T1D also spend less time in physical activity than healthy individuals 15,16 . They fear experiencing hypoglycemia during and after exercise, given the negative effects of the condition 15,17,18 . It has been reported that presenting the benefits of physical activity to children with T1D will help lessen their fears 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been noted that children with T1D also spend less time in physical activity than healthy individuals 15,16 . They fear experiencing hypoglycemia during and after exercise, given the negative effects of the condition 15,17,18 . It has been reported that presenting the benefits of physical activity to children with T1D will help lessen their fears 19 .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 They fear experiencing hypoglycemia during and after exercise, given the negative effects of the condition. 15,17,18 It has been reported that presenting the benefits of physical activity to children with T1D will help lessen their fears. 19 However, most of the evidence comes from studies that used treadmill or cycle ergometers.…”
mentioning
confidence: 99%
“…Peer support has been shown to improve glycemic control, alleviate negative emotions and improve the quality of life among patients with type 1 diabetes 10 , 11 , 12 , 13 . Traditionally, peer support among patients with type 1 diabetes is implemented by focus groups, diabetes camps and face‐to‐face training sessions 14 , 15 , 16 . However, several barriers prevent patients with type 1 diabetes from benefitting from peer support, including inflexible schedule, inaccessible social network, low socioeconomic status and remote residency 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey based on self-and parent-report revealed that 28% of youth with T1D aged 9 to 17 years were insufficiently active [3]. Among the multiple barriers to engaging in a physically active lifestyle, T1D-specific major barriers include fear of hypoglycemia and insufficient knowledge of managing diabetes around exercise [4][5][6]. Empowering individuals with T1D to manage their blood glucose levels during exercise is a complex challenge faced by health care professionals, as many factors can influence an individual's glycemic response to exercise, such as exercise type, intensity, and duration [7,8]; fitness levels; insulinemic state [9]; environmental conditions; and anxiety and stress levels [10].…”
Section: Introductionmentioning
confidence: 99%
“…Current care models provide very limited physical activity support to people with T1D. Previous research conducted by our team proposed that providing exercise guidelines in a mobile health (mHealth) app would be useful as a decision-support aid around exercise management for adolescents and young adults with T1D [6]. Global use of mHealth apps is on an exponential rise, and these tools provide a useful platform to deliver health behavior interventions [16][17][18].…”
Section: Introductionmentioning
confidence: 99%